Characterisation of AlScZr and AlErZr alloys processed by rapid laser melting. (1st July 2018) - Jia, Qingbo; Rometsch, Paul; Cao, Sheng; Zhang, Kai; Huang, Aijun; Wu, Xinhua
Abstract: AlScZr and AlErZr alloys with Sc or Er additions of ~0.6 at.% were prepared by a novel wedge mould casting and laser remelting methodology. Precipitation strengthening and thermal stability were studied using hardness testing and transmission electron microscopy. After ageing, the AlScZr alloy achieved a peak hardness of 113 HV0.5 and possessed pronounced thermal stability, while the AlErZr alloy obtained a maximum hardness of 84 HV0.5 and experienced relatively rapid over-ageing. Compared with Sc, the lower solubility of Er even after laser remelting and its more rapid diffusivity are responsible for the relatively lower ageing response and poorer thermal stability. Graphical abstract: Unlabelled Image